Developing an Approach to Compress Non-Repetitive Codecs of DNA Using a Novel NDCP: A Lossless Utility - Prasad , V.Hari (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2016)
The transformation has been started with Information Theory in the field of Data compression. The outcome of data compression is a technological explosion in internet technology, now the continent is enjoying. Initially the spark of compression has been welded with Text (Lossless) compression and later it has been speeded to the allied areas like Geneti (DNA&mRna) and multimedia data compression (Lossless&Lossy). In 2004 the Human Genome project was deciphered. Can you imagine the human genome requires in an around of 30-35 GB for storage and maintenance. If at all if would have to maintain census data bases the infrastructure would requires substantially larger. So the remedy is compression of genetic sequences. Due to arrival of different DNA sequences the public genetic databases size growing like in an exponential manner. To limit it state of the art many DNA compression algorithms were strived into the compression era, but they work with common performance analysis of best, worst and avg cases based on repetitiveness of the DNA sequences. In case if DNA contains many non frequent fragments(non-codecs) the existing techniques may run in worst case. A new methodology is highly inevitable for non codec’s. In this work a Lossless novel utility Tool NDCP (Non-codecDNAcompression) was proposed to delimit the feasible compression ratios of existing compression techniques.